2014
DOI: 10.1016/j.sajb.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Fire and the reproductive phenology of endangered Madagascar sclerophyllous tapia woodlands

Abstract: International audienceKeywords: Reproductive phenology Fire Tapia woodland Uapaca bojeri Ibity mountain Tapia woodland vegetation is a remnant of Madagascar sclerophyllous forest that has developed under the selective pressure of fire and is dominated by the endemic tree Uapaca bojeri (Phyllanthaceae), locally named tapia. We carried out a 2-year study in tapia woodland at Ibity mountain, a new protected area in central highlands of Madagascar. We aimed to describe the reproductive phenology of this vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 49 publications
3
30
1
2
Order By: Relevance
“…The timing of fire occurrence is also relevant to determine the damages to leafing, flowering, fruiting and/or germination processes, impacting seedlings and reducing recruitment, as well as favoring specific groups of species that are fire tolerant or fire resistant (Alvarado et al, 2015(Alvarado et al, , 2014Hoffmann, 1998). The peak in active fires, observed on MODIS data from Serra do Cipó between the end of the dry season and the beginning of the wet season (September and October), is consistent with other cerrado studies.…”
Section: Discussionsupporting
confidence: 85%
“…The timing of fire occurrence is also relevant to determine the damages to leafing, flowering, fruiting and/or germination processes, impacting seedlings and reducing recruitment, as well as favoring specific groups of species that are fire tolerant or fire resistant (Alvarado et al, 2015(Alvarado et al, , 2014Hoffmann, 1998). The peak in active fires, observed on MODIS data from Serra do Cipó between the end of the dry season and the beginning of the wet season (September and October), is consistent with other cerrado studies.…”
Section: Discussionsupporting
confidence: 85%
“…Fruit production and dispersal of tapia woodland species occur mainly during the rainy season, between November and May (Alvarado et al . ), a pattern that is also observed in some other tropical ecosystems, such as the Cerrado (Batalha & Mantovani ; Weiser & Godoy ) and the Atlantic forests (Morellato et al . ) of Brazil.…”
Section: Introductionsupporting
confidence: 59%
“…A phenology study performed on selected woody tapia woodland species (Alvarado et al . ) showed that seed dispersal takes place during the rainy season for five of the species studied: A. ibityensis , A. theiformis , C. edulis , U. bojeri and V. secundiflorum . Seed germination of these and other woody species is potentially linked to rainfall because precipitation brings an increase in soil moisture, which promotes germination (Oliveira & Silva ; Baskin & Baskin ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example reproductive phenology of the individuals in group three, did not show any relation with the evaluated micro-environmental variables. Other random factors, or the genetic constitution of individuals, plant diseases, pollination interactions, dispersal and predation can influence the variability of reproductive patterns (van Schaik et al 1993, Cuevas-García et al 2013, Alvarado et al 2014. Likewise, the temporal variability between years can display the relation between environmental factors and the production of reproductive structures at a finer scale (Sherry et al 2007).…”
Section: Discussionmentioning
confidence: 99%